Pourquoi les théories discursives peuvent avoir du mal à entrer en classe de langue(s) étrangère(s) - Gajewska, Elżbieta (Studia Romanica Posnaniensia, 2017)
The fact that verbal expression is subject to both language and social norms is indisputable. However, the advances of discursive theories are slow to be integrated into didactic practice in a systematic way. The article attempts to identify reasons underlying such a state of affairs. It is argued here that the overabundance of reference theories and the different scientific traditions lead to the fragmentation of the object of the study and create false terminological friends. The use of units of conceptualization and analysis of discourse, such as the genre or type of discourse, sometimes poses problems in didactic practice. Finally, discursive norms evolve continuously, often creating hybrid forms. One of the solutions to the above-mentioned problems, proposed in this article, is to make learners aware of discursive phenomena rather than try to provide ready-made solutions.